Church activity of Włocławek’s Bishops in period of Kujawsko – Kaliska Diocese - GRĘŹLIKOWSKI, JANUSZ (Prawo Kanoniczne, 2013)
Diocesan Bishop, who „from God’s appointment takes the place amongst the Apostles and he is that appointed Shepherd in the Church, so he can be the teacher of tuition, priest of God’s worship and venerable of ruling” (can. 375 § 1 of Code of Canon Law) Decides about the condition of the Diocese – particular Church, its life and priesthood life as well as organization of particular Church that is under bishop’s management depend on his activity and established legal standards. In the history of Włocławek’s diocese, many great, outstanding, educated and experienced reform – making shepherds were sat on Bishops’ capital. Amongst the others, some of them and their legacy include Włocłąwek’s bishops, who acted in difficult period of XIX and beginning of XX century, the period called kujawsko-kaliski period in history of Włocławek’s diocese, which took place in years 1818 – 1925. That period was one of the most difficult time that Włocławek’s Church experienced and went through over a span of its history. It was caused not only by the fact that Poland lost its sovereignty and also due to a fact that nation, which was catholic and areas of Włocławek’s diocese were ruled by goverments, which were in majority non-catholic. It had an impact on many areas Church life in the Diocese and had significant influence on the way the diocese was managed by Włocławek’s bishops. Many times they were required to undertake determined actions having in purpose to defend Polish provenance and rights as well as a possibility to maintain the priesthood by the Church and providing the God'’ worship. Thanks to prudence and efforts of Bishops, despite of taking away from Church its former wages, it was possible in described period to get from government authorities quite big funds for construction of churches, seminaries or renovation of the cathedral. In the same time, the bishops of period in question undertook various actions having in purpose to maintain Polish descent on the flock residing on area of diocese as well as aiming at keeping the rights of the Church, correct life and functioning of different Church offices and realization of principal mission of the Church. The first bishops of period in question, not knowing the tradition of diocese, resided in Kalisz, however thanks to determined attitude of Włocławek’s chapter, wchich defended the rights of Włocławek and local cathedral, opposing to attempts for transferring the whole diocese centre to Kalisz, decided to transfer the central offices to the old capital in Włocławek and to reside in Włocławek. Because of that the capital of primeval Włocławek dioces, despite of its rough history and many administrative-organizational changes it had to be subjected to, had always remained the same. Bishops also took a great care of material, religious and priesthood condition of Włocławek’s Church. Many of them were the great shepherds and administrators, intellectualists and national campaigners, politicians and senators, demanding and fighting for rights for Polish nation, which was then under foreign annexations. Thanks to their activity Włocłąwek’s Church owed so much to them in areas of religious, priesthood, administrative and legislative life. By taken appropriate church actions, bishops had significant influence on shape, picture and life of diocese then. We should especially emphasize and appreciate the activity of four bishops from period in question, and namely: Józef Ignacy Rybiński (1777 - 1806), Jozef Szczepan Koźmian (1823 - 1831), Aleksander Kazimierz Bereśniewicz (1883 - 1902) and Stanisław Kazimierz Zdzitowiecki (1902 – 1927), whim we can include to circle of outstanding Włocławek’s shepherds of described period.